State-of-Art review on deployable scissor structure in construction. (August 2022) - Moy, Jian Jun; Tan, Cher Siang; Mohammad, Shahrin; Abidin, Ahmad Razin Zainal
Abstract: Deployable structures are flexible structures that can transform themselves from a stowed state to a deployed state with a predetermined configuration upon actuation. Based on existing studies, there are various types of deployable structures that can generally be classified based on their applications and structural components. Amongst the varieties, scissor structure stands out as one of the most well-known deployable structures with great structural strength and flexibility. Drew on existing studies, it was observed that the research on structure has advanced in terms of mechanisms, practical applications, design, and analysis methodology. In this state-of-art review, the development of various types of scissor structure based on 61 papers over the past two decades was explored extensively and critically discussed based on a significant categorisation. Generally, it was found that new scissor structures were developed to improve their structural stiffness, flexibility, and practicality by modifying their existing element configuration, joint type, and actuation method. Furthermore, this review presented the development of the design and analysis method for scissor structures. Based on existing studies, it was found that various configurations of scissor structure were developed to suit various applications. However, the scissor structure is still not widely implemented in the industry due to insufficient research that had focussed on its structural analysis. In this paper, research gaps and the future prospect of scissor structure were presented.